2017
DOI: 10.5539/ijbm.v12n11p187
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Adoption of Islamic Banking in Malaysia

Abstract: A nation's economic success is largely dependent on the performance of their banks as they play a major role in regulating its financial sector to stability and cohesion by acting as an intermediary to various parties such as individuals, organizations and governments to conduct their borrowing and depositing activities. The quality of services provided by the banks will influence how these parties benefit and consumers would choose the bank that they perceive will result in the most benefit. In Malaysia, a la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…(Anthony Mariadas & Murthy, 2017). According to Islamic principles, the only way for Muslim bank customers to benefit from trade and investment as a means of revenge is when exposed to risk through the risk-sharing method.…”
Section: Risk Perception (Rp)mentioning
confidence: 99%
See 1 more Smart Citation
“…(Anthony Mariadas & Murthy, 2017). According to Islamic principles, the only way for Muslim bank customers to benefit from trade and investment as a means of revenge is when exposed to risk through the risk-sharing method.…”
Section: Risk Perception (Rp)mentioning
confidence: 99%
“…Previous research only examined the acceptance of Islamic banking and its impact on Islamic financial literacy (Zaman et al, 2017). The adoption of Islamic banking also affects risk perceptions (Anthony Mariadas & Murthy, 2017) and under subjective norms (Jaffar & Musa, 2016) based on the literature, it can be said that the AIB also affects perceptions and behavior control (Albashir et al, 2018). On behalf of the literature, we say that this is the first type of study that examines the influence of Islamic financial literacy, risk perception, subjective norms, and behavioral control on the acceptance of Islamic banking evidence from Pakistan.…”
Section: Introductionmentioning
confidence: 99%
“…Mariadas and Murthy (2017) also agreed that the degree of how much a customer will look into a product is influenced by the consumer's prior knowledge about a product. The in-depth knowledge and understanding which customer have towards the product or service will have a positive impact on its satisfaction.Thus, the banks have to make sure that the customers have the correct information regarding a product to avoid the misconception and miscommunication among customers that could cause them to lose interest in the products offered (Mariadas & Murthy, 2017). It also recognized by Adrutdin et al (2016) which revealed that the lack of information and knowledge about a particular banking products has significantaffect on the customers' interest to purchase the products.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, one of the measures to be taken in Islamic financial planning is the selection of a trusted Islamic banking product. (Noh et al, 2020).It is also backed by Adrutdin et al, (2016) which stated that it is necessary for a banking institution to deliver the knowledge of Islamic financial planning and understanding of Islamic credit cards to the public and this matter should not be taken for granted as it would in a way affect customer satisfaction (Mariadas & Murthy, 2017). So that, it is unquestionable that customers' satisfaction is essential in all styles of businesses as the most effective approach to improve and maintain customer base via attaining high customer satisfaction (Chee, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…This figure can be said to be low when viewed from the rapid growth of the Islamic economy in Indonesia which was reported to have reached 81.93 points [2]. The low market share of Islamic banks shows that public interest is still low due to market competition conditions between Islamic banks and conventional banks [3] [4]. In addition, public doubts about Islamic banks have affected their level of trust in Islamic bank's operations which is not good enough [5] [6].…”
Section: Introductionmentioning
confidence: 99%